1993
DOI: 10.1002/stem.5530110614
|View full text |Cite
|
Sign up to set email alerts
|

The infusion of human fetal liver cells

Abstract: Only transient engraftment of infused fetal liver cells has been demonstrated in a small proportion of patients with hypoplastic bone marrow or patients undergoing treatment for acute leukemia. This presumably reflects the ability of the recipient to reject the infused cells, the infusion of too few viable stem cells or the availability of too few accessory cells; it is clear from the successful engraftment of infused fetal liver cells in a high proportion of infants and fetuses with severe immunodeficiency di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Present work was carried out to elucidate the mechanism of autologous recovery observed in some patients treated with FLI therapy, with a special focus on variable responses obtained even in a single clinical group [1][2][3][4][5][6][7][8][9][10][11]. As a first step towards this goal, we carried out experiments to check whether FLHC themselves could stimulate normal adult human BM progenitors, and if they do, then by what mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Present work was carried out to elucidate the mechanism of autologous recovery observed in some patients treated with FLI therapy, with a special focus on variable responses obtained even in a single clinical group [1][2][3][4][5][6][7][8][9][10][11]. As a first step towards this goal, we carried out experiments to check whether FLHC themselves could stimulate normal adult human BM progenitors, and if they do, then by what mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, activation of Fas has been reported in CD34 + progenitor cells from aplastic anemia patients [51]. Since the utility of FLI therapy in disorders such as aplastic anemia has been underscored by clinical as well as experimental studies [1][2][3][4][5][6][7][8][9][10][11], it would be important to check whether FLHC treatment and the attendant success in aplastic anemia correlates to the Fas activation profiles on their progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also has been suggested that fetal liver cells may promote the recovery of autologous hematopoiesis and inhibit proliferation of leukemic cells (Thomas, 1993). One retrospective study found a higher rate of complete remission (65%) in patients who received fetal liver cell infusions following treatment for acute myeloid leukemia than in those patients who did not receive fetal liver cells (36%) (Wang, 1992).…”
Section: Fetal Livermentioning
confidence: 98%